The IMPACT of LOAD-SHEDDING on a COMPANY in MINING INDUSTRY - Tshinavha, Londani; Ukpere, Wilfred (Journal of Economic Development, Environment and People, 2024)
South Africa, a major energy producer, relies on Eskom, its state-owned power supplier, for all electricity, which is crucial for various sectors, especially mining. The mining sector consumes about 30% of Eskom’s supply, impacting employment and the country’s gross domestic product significantly. However, increased electricity demand and Eskom’s struggles to meet the demands has led to load shedding since 2015, impacting mining operations negatively. Therefore, this study aimed to explore the impact of load shedding on a mining company’s operations in the Brits area. A qualitative approach was adopted to ascertain the study participants’ opinions of the impact of load shedding on a mining company’s operations. The purposive sampling technique was used to select participants who had adequate knowledge and experience of how load shedding impacts mining operations. Data was collected from 10 participants through face-to-face semi-interviews. Thematic analysis was employed to identify, organise and report the themes that emerged from the data set. The findings revealed that load shedding impacted the mining company’s overall operations negatively, ranging from loss of production to high operational costs, work stoppages, system disruptions, revenue losses and poor network connectivity. The study provides an adequate understanding of how load shedding impacts the operations of mining companies. The study has practical and managerial implications for mining companies in South Africa because it provides measures to address the impact of loadshedding on mining operations. The study recommends that mining companies should invest in alternative energy power sources such as solar power, generators, and catch-up plans